Spin‐Dependent Processes Measured without a Permanent Magnet. Issue 41 (7th May 2018) - Fontanesi, Claudio; Capua, Eyal; Paltiel, Yossi; Waldeck, David H.; Naaman, Ron
Abstract: A novel Hall circuit design that can be incorporated into a working electrode, which is used to probe spin‐selective charge transfer and charge displacement processes, is reviewed herein. The general design of a Hall circuit based on a semiconductor heterostructure, which forms a shallow 2D electron gas and is used as an electrode, is described. Three different types of spin‐selective processes have been studied with this device in the past: i) photoinduced charge exchange between quantum dots and the working electrode through chiral molecules is associated with spin polarization that creates a local magnetization and generates a Hall voltage; ii) charge polarization of chiral molecules by an applied voltage is accompanied by a spin polarization that generates a Hall voltage; and iii) cyclic voltammetry (current–voltage) measurements of electrochemical redox reactions that can be spin‐analyzed by the Hall circuit to provide a third dimension (spin) in addition to the well‐known current and voltage dimensions. The three studies reviewed open new doors into understanding both the spin current and the charge current in electronic materials and electrochemical processes. Abstract : A novel Hall circuit design is used as a working electrode. Three different types of spin‐selective processes have been studied with this device in the past: photoinduced charge exchange between quantum dots and the working electrode through chiral molecules, charge polarization, and cyclic voltammetry measurements of electrochemical redox reactions that can be spin‐analyzed.